533 TREATMENT AND OUTCOMES OF MERKEL CELL CARCINOMA AT UCSF. (1st January 2006) - Tan, C.; Florero, M.; Leong, S. P.L.
Abstract : Background: Cyril Toker first described merkel cell carcinoma (MCC), a rare, aggressive, neuroendocrine carcinoma of the skin, in 1972. Purpose: The aim of our study is to review the UCSF experience of treating MCC from 1989 to the present time. Method: A retrospective study using a database of patients treated and followed at UCSF Hospitals. Results: There are 68 patients with MCC presenting on the head and neck (33), extremities (23), torso/trunk (3), vagina (1), parotid gland (1), and NOS (7). To date, 40 of 42 patients are still alive and disease free. The other 2 patients had recurrence as multiple distant metastasis and invasion into adjacent organs. At this time, additional clinical outcome information is being gathered. Conclusion: A significant number of patients had MCC in the head and neck region. The mortality rate of MCC at UCSF is 38.2% at the present time. I would like to thank the University of British Columbia MD/PhD Program and CIHR for their support.